2003
DOI: 10.1007/s00421-003-0830-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prolonged intermittent high-intensity exercise on knee flexor strength in male and female soccer players

Abstract: This study investigated the effect of an acute, prolonged, intermittent, high-intensity single-leg pedalling exercise task (PIHIET) on the isokinetic leg strength of the knee flexors in six male and seven female collegiate soccer players. Following determination of single-leg VO(2peak), subjects completed a PIHIET designed to simulate the energetics of soccer match play (approximately 90 min in total; approximately 70% single-leg VO(2peak)). Pre-, mid- and post-PIHIET gravity-corrected indices of knee flexion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Mercer et al (2003) reported a 22% decline in peak torque of the knee flexors following 90 min intermittent cycling. Using a treadmill-based exercise protocol to induce fatigue, Rahnama et al (2003) showed that strength performance of both quadriceps and hamstrings of college level players were significantly reduced from pre-exercise to half-time and from half-time to post-exercise at all angular velocities.…”
Section: Isokinetic and Isometric Muscle Function Of The Knee Extensomentioning
confidence: 99%
See 2 more Smart Citations
“…Mercer et al (2003) reported a 22% decline in peak torque of the knee flexors following 90 min intermittent cycling. Using a treadmill-based exercise protocol to induce fatigue, Rahnama et al (2003) showed that strength performance of both quadriceps and hamstrings of college level players were significantly reduced from pre-exercise to half-time and from half-time to post-exercise at all angular velocities.…”
Section: Isokinetic and Isometric Muscle Function Of The Knee Extensomentioning
confidence: 99%
“…A number of studies have attempted to describe the temporal aspects of the decay in muscle strength during soccer-simulation studies (Greig, 2008;Mercer, Gleeson, & Wren, 2003;Rahnama, Reilly, Lees, & Graham-Smith, 2003). Mercer et al (2003) reported a 22% decline in peak torque of the knee flexors following 90 min intermittent cycling.…”
Section: Isokinetic and Isometric Muscle Function Of The Knee Extensomentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to data analysis, investigators using soccerspecific fatiguing protocols might consider the angle at which peak torque is attained and, in more detail, the torque curve time-history, as others 26 have shown discrepancies among angles with single-leg pedaling exercises. The relevance of peak torque to injury incidence data should naturally be treated with some caution.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…[1][2][3] Many of these injuries are believed to occur during single-leg landings, with no direct blow to the knee. [4][5][6] Although the causes of these injuries are not known, they are widely believed to include some combination of environmental, biomechanical, neuromuscular, structural, and hormonal factors. [7][8][9] Authors 10-12 studying biomechanical and neuromuscular risk factors for ACL injury have suggested that weakness of muscles that abduct the hip, such as the gluteus medius, may predispose an individual to greater hip adduction or internal-rotation excursion during weight-bearing activities such as jumping or landing.…”
mentioning
confidence: 99%